Penerapan Model Discovery Learning dalam Pembelajaran IPA untuk Meningkatkan Keterampilan Siswa SDN 3 Baledono - Syahla Nadya Laelatulfi; Rosita Rahmawati; Lutfiyatul Fahmi; Nur Ngazizah (Indonesian Journal of Elementary and Childhood Education, 2023)
Discovery learning is a learner-centered discovery learning model. This model involves critical, logical, and systematic thinking skills. Discovery Learning is rightly applied to high grades, especially grade 5. The Discovery Learning model is also effectively used in all lessons. However, in science lessons this model will be more effective if applied properly. Because this model is based on discovery which is closely related to science lessons, which do a lot of experiments and observations. The Discovery Learning model provides opportunities for students to explore themselves and their environment. This opportunity can develop their behavior and potential. Students also gain new skills, experiences, and understandings. In addition, the teacher as an educator is tasked with only assisting the process of running this model. The teacher only gives advice and motivation to do the Discovery Learning model. This model aims to improve the thinking ability of students to become more active and confident in the learning process in the classroom and outside the classroom.